A Trinidad Bathing Beach, B.W.I. - A27757 - (:unkn) unknown (My University, 2009)
Bathers enjoying the waters of the ocean at Maracas Beach and the background, a forested mountain range.
Colour; Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Maracas Bay; Beaches